The Uniqueness of ‘Ali Al-Shabuni’s Methodology in the Book of Shafwah Al-Tafasir: Study to the Interpretation of Surah Al-Rahman - Abdul Hafidz; Khoirul Ulum; Muhammad Ridlwan Nasir; Idri Idri; Mohammad Arif (Alliance of Health Activists (AloHA), 2021)
The Qur'an has proven to have inspired and produced many tafseer books with various approaches, methods and interpretive tendencies. The book of Shafwah Al-Tafasir is a contemporary tafseer hwo has written by Ali Al-Shabuni which has a unique and distinctive methodology. Because of this, this article aims to examine the exegetical methodology applied by Ali Al-Shabuni in interpreting surah Al-Rahman and to find out the advantages and weaknesses of its methodology. The results of this study indicate that the uniqueness of the methodology applied by Al-Shabuni in interpreting surah Al-Rahman is combine the riwayah and dirayah approaches and the tahlili and ijmali methods. In addition, it also use the tendency of al-adabi al-ijtima’i and the systematic, and contemporary interpretive techniques with additional footnotes to make it easier for readers to refer to the original source. As well as, the Ali Al-Shabuni’s methodology in the Book’s Shafwah Al-Tafasir has the advantages and the weaknesses. Keywords: Surah Al-Rahman; ‘Ali Al Shabuni; Shafwah Al-Tafasir; uniqueness; methodology; interpretation